UPAYA PERBAIKAN SIFAT MEKANIK BAJA PLAT JOIN G 3131 SPHC MELALUI SIMULASI PROSES INTERCRITICAL ANNEALING DI INDUSTRI KONSTRUKSI BAJA - Fathoni, Imam Nur; Alfirano, Alfirano; Muljono, Djoko (Jurnal Rekayasa Mesin, 2023)
Improvement of the mechanical properties of G3131 SPHC equivalent to JIS G 3101 SS330 plate joint steel through intercritical annealing simulations has been carried out. The JIS G 3131 grade SPHC steel was gradually heated by intercritical annealing at temperatures of 750–850 oC for holding times of 1–15 minutes. After intercritical annealing treatment, the tensile strength and yield strength of steel increased compared to non-treatment samples. The average tensile strength obtained was 573 MPa with an increase of 76.85% compared to the tensile strength before the intercritical annealing process. Meanwhile, the yield strength of steel increased by 60% to 421 MPa. Increasing the annealing temperature and holding time will promote the formation of the martensite phase, as well as enlarge the austenite and ferrite grains. Optimal heating variable obtained at a temperature of 750 ℃ with a holding time of 15 minutes. Using these variables produced a tensile strength of 625 MPa and a yield strength of 434 MPa with an elongation of 23% which is standardly included in JIS G 3101 SS400.At the optimal value, the grain growth kinetic of K and n values were 0.280466778 and 0.6905, respectively, with an activation energy (Q) of 12.4268517 J/mol.